Growth characteristics of three Sphagnum species in restored extracted peatland. Issue 6 (3rd September 2020) - Karofeld, Edgar; Kaasik, Ants; Vellak, Kai
Abstract : Peatlands are essential ecosystems in global carbon cycle. However, they have been drained for economic benefits for centuries; large peatland areas have turned from carbon storage ecosystems to the carbon emitters. Because of the slow spontaneous revegetation of abandoned extracted peatlands, there is urgent need for their active restoration, required also for mitigation of global climate change effects. The selection of Sphagnum species suitable for restoration may also have crucial effects to reach the restoration aims. In 2012, we began a restoration experiment in abandoned extracted peatland in central Estonia. We aimed to elucidate whether Sphagnum species, specific to natural North European bogs, have different growth characteristics under altered growth conditions in restored extracted peatland. We studied growth characteristics of S. fuscum, S. medium, and S. rubellum at restoration sites with two different water table levels and in two natural bogs. We estimated total cover of Sphagnum carpet and cover of three target species and measured shoot growth characteristics at each site. Linear models with correlated errors were used for temporal trends studies. Our results showed that studied Sphagnum species have different growth characteristics in restoration sites and that the main growth promoter is the water table depth (WTD). Results showed that greater Sphagnum cover (over 70%) can be achieved in wetter conditions with WTD higher than circa 20 cm. On wetter restoration sites S. medium and S. fuscum could be recommended for restoration, whereas S. fuscum perform well also in drier sites.